MINAT MAHASISWA PROGRAM STUDI D4 MANAJEMEN PERHOTELAN JURUSAN PARIWISATA FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG MELAKSANAKAN PENGALAMAN LAPANGAN INDUSTRI DI INTERNATIONAL CHAIN HOTEL - Junita Riza (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
This study aims to determine the interest of D4 hospitality management study program students in tourism and hospitality faculties of Padang State University to carry out industry experience in international chain hotel. This type of research is quantitative descriptive with survey methods. Samples were taken using purposive sampling technique with 83 respondents used questionnaires on the Guttmann scale. Based on the research that has been done, the results are as follows: (1) feeling happy in the very high category (59,03%), (2) attraction is in the very high category (50,60%), (3) attention is in high category (42,16%) and involvement is in the very high category (44,57%).